Desproporcionalidad de las multas de urbanismo por parte de la alcaldía local de Santa Fe en el distrito capital de Bogotá 2015-2018 (2018)
Due to the constant questioning of people who have been affected by disproportionate sanctions and violations of rights such as protection for the elderly, minors, vulnerable population, displaced by violence among others, by the Local Mayors' Offices, it is necessary know in depth the application of Law 810 of 2003 and 1801 of 2016 in terms of urban sanctions in order to determine its proportionality, legality and adequate application with respect to the purposes of the State. Identify the disproportionality between the fault committed and the sanction granted, in order to request the legislator to adapt the rule taking into account social, economic factors and vulnerability conditions.